A Review of “Shamāʾil al-Ḥabīb al-Muṣṭafā” by Muhammad al-Ya‘qoubi - Mete Gezer (Darulfunun Ilahiyat)
Muhammed el-Ya’kûbî. Şemâilu’l-Habîbi’l-Mustafâ. (İngiltere: Signatora, 2023. 250 s.) ISBN: 978-1-913258-35-1